Peningkatan Kesadaran Kesehatan Dalam Masyarakat Melalui Pengecekan Tensi Dan Gula Darah Di RT 04/RW 08 Kelurahan Rempoa - Anggun Nurul Chasanah; Suyudi Alimun Hakim; Muhammad Farrel Shaumi; Renty Anugerah Mahaji Puteri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
In this KKN-UMJ 2022 activity, our group took the theme of health in organizing a work program "Increasing Health Awareness in the Community through Checking Tension and Blood Sugar in RT 04 / RW 08 Rempoa Village", in this work program we chose partners in RT 04 / RW 08 Rempoa Village, East Ciputat District, South Tangerang City, because they saw the rise of hypertension and diabetes in the community. The method of implementation carried out in this activity is carried out by offering an examination of blood pressure (tension) and blood sugar then followed by the presentation of material about blood pressure (tension) and blood sugar. After the check was carried out, the test post was given by distributing a questionnaire that tested public knowledge about blood pressure (tension) and blood sugar. After this work program was carried out, there was a significant increase in public knowledge about blood pressure (tension) and blood sugar.